2016
DOI: 10.1371/journal.pone.0147170
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mesenchymal Stromal Cell Therapy for Acute Lung Injury in Preclinical Animal Models: A Systematic Review

Abstract: The Acute Respiratory Distress Syndrome (ARDS) is a devastating clinical condition that is associated with a 30–40% risk of death, and significant long term morbidity for those who survive. Mesenchymal stromal cells (MSC) have emerged as a potential novel treatment as in pre-clinical models they have been shown to modulate inflammation (a major pathophysiological hallmark of ARDS) while enhancing bacterial clearance and reducing organ injury and death. A systematic search of MEDLINE, EMBASE, BIOSIS and Web of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(110 citation statements)
references
References 63 publications
(335 reference statements)
4
105
1
Order By: Relevance
“…Systemic administration of autologous and allogeneic MSCs has been uniformly demonstrated as safe in a wide range of diseases, without infusion‐related toxicity or significant adverse effects over at least 5 years after administration, as shown in recent meta‐analyses 28. Preclinical studies have also demonstrated the safety of intrabronchial MSC administration, and a small number of trials support the clinical safety of this approach 27.…”
Section: Discussionmentioning
confidence: 95%
“…Systemic administration of autologous and allogeneic MSCs has been uniformly demonstrated as safe in a wide range of diseases, without infusion‐related toxicity or significant adverse effects over at least 5 years after administration, as shown in recent meta‐analyses 28. Preclinical studies have also demonstrated the safety of intrabronchial MSC administration, and a small number of trials support the clinical safety of this approach 27.…”
Section: Discussionmentioning
confidence: 95%
“…We utilized 47 English language studies there were previously identified in a systematic review of acute lung injury and MSCs [15]. A detailed protocol for the systematic was pre-registered [29] and published [16] prior to conducting the research.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed protocol for the systematic was pre-registered [29] and published [16] prior to conducting the research. A list of the included studies is included in S1 Table and general characteristics of the included studies are published in our systematic review [15]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other cellular options such as mesenchymal stromal/stem cells, have not demonstrated efficacy beyond a small anti-inflammatory paracrine affect (Stabler, Lecht et al 2015, Ikonomou, Freishtat et al 2016, McIntyre, Moher et al 2016). In contrast, the use of iPSCs to generate lung cell lineages for replacement of cells due to acute injury or disease related loss, could eventually be used for regenerative purposes.…”
Section: Promoting Adult Lung Regeneationmentioning
confidence: 99%